Mathematical teacher efforts to develop student's critical thinking skill - Mohamad Aminudin; Imam Kusmaryono (STKIP PGRI Banjarmasin, 2019)
: The purpose of this study is to evaluate mathematics learning by looking at the efforts of mathematics teachers in developing students' critical thinking skills in the classroom. Methods: This qualitative research explores the mathematics teacher's efforts in developing critical thinking skills. Two mathematics teachers were selected, observed and interviewed about mathematics learning in the classroom, the learning environment that was wanted to be created, and the assessment carried out. The results of the observations combined with the results of the interview found several conclusions that the two mathematics teachers had not tried maximally in learning mathematics to develop students' critical thinking skills. Both subjects have not created an effective learning environment. In addition, the assessment of mathematics learning outcomes is still done at the end of learning